Shell Characteristics of Eggs from Historic Strains of Single Comb White Leghorn Chickens and the Relationship of Egg Shape to Shell Strength - Anderson, K.E.; Tharrington, J.B.; Curtis, P.A.; Jones, F.T. (International Journal of Poultry Science, 2003)
The effect of long term genetic selection on shell characteristics was determined by analyzing eggs acquired from Agriculture Canada: Ottawa Control Strain 5, from a 1950 base population; 7, from a 1959 population; and 10, from a 1972 population. H&N "Nick Chick" 1993 commercial strain was also included because it shares genetic ancestry with the three historic strains. Eggs were collected beginning at 28 wk of age, then every 4 wk through the end of the study at 86 wk of the laying cycle and egg weight, egg height, egg width, shell weight, shell thickness, egg specific gravity, and shell breaking force measured. The relationship of egg shape and weight as factors affecting shell strength were also investigated. Significant differences (P < 0.05) were found between strains for egg shape and a progressive increase in weight and surface area of eggs from the 1950 strain to the current strain. The shape index indicates that the current strain has increased egg size with the greatest increase seen in egg width. The mean breaking force of eggs from the current strain was higher (P< 0.05) than the other strain`s eggs with no strain differences in percent shell weight, shell thickness, or specific gravity. A decline in breaking force, percent shell weight, and specific gravity was observed among all the strains over the production period. The results from this study suggest that genetic selection has produced larger eggs that are rounder in shape.